Analisis Kinerja Pendapatan Asli Daerah pada Pemerintah Kabupaten/Kota di Provinsi Aceh Tahun Anggaran 2017 2021 - Ilham, Ikhsanul; Suparno, Suparno (Syiah Kuala University Press, 2024)
This study aims to examine and analyze the Local Own-Resource Revenue in Aceh Province during the fiscal years 2017-2021. The population includes the Financial Reports of Local Governments in the Aceh Province from 2017 to 2021. The data utilized is secondary data extracted from the Financial Reports of Local Governments in the Aceh Province for the period 2017-2021. The research employs a descriptive method with a qualitative approach for data analysis. The results reveal that the financial autonomy of all local goverment the Aceh Province in meeting the financing needs for governmental tasks, services, and development is consistently low each year. The central government continues to have a more dominant role in fulfilling the financing requirements for governmental tasks, services, and development compared to the role of Local goverment in the Aceh Province. The findings of this research are anticipated to offer insights and considerations for local governments in formulating policies for managing the Aceh Regional Revenue and Expenditure Budget (APBA).